Keberadaan Bakteri Legionella Pada Ruangan Ber AC dan Karakteristik Serta Keluhan Kesehatan Pegawai di Kantor Gubernur Sumatera Utara Tahun 2014 - Ira Putri Lubis; irnawati marsaulina; surya dharma (Lingkungan dan Kesehatan Kerja, 2014)
Using the air conditioner as an alternative to replace natural ventilation was to make comfortable and to improve the productivity. However the use of air conditioner that was not well maintained becomes a good media for microbial growth such as legionella. Legionella was live and breeds easily in humid and warm environment, which was suitable in the AC equipments like cooling tower. This research was to identify the existence of legionella in the room using air conditioner, the characteristics of the staffs and their health complaint. The research location in Sumatera Utara governmental building at Jalan Diponegoro No 30 Medan. The type of this study was descriptive, the number of population were 95 staffs who were working at Biro Protokol room and Biro Pemerintahan room. Samples were total sampling technique. Data were tabulation and presented by table and analyzed descriptively. The result of this study showed that the most staffs were 31-40 years old (38,9%). education level was senior high school (44,2%), the most staffs have been working more than 5 years (77,9%), staffs working more than 8 hours/day was 63,2%. The staffs were not smoker (71,6%) and the staffs who don’t have allergic to cold air was 88,4%. Laboratorium result showed legionella was found at cooling tower and the room using air conditioner. There are 67 staffs having health complaint and the most health complaint were sore throat . This study conclude that using of AC central which was not well maintained may increase the growth of legionella and causes the health complaint for the staffs. The suggestion for Sumatera Utara government was to check the Air Conditioner once every three months and to promote the staffs to participate in keeping the working area clean. Keywords : Legionella, The room air conditioner, Staffs Characteristic, HealthComplaint